A new binary PSO with velocity control - Lanzarini, Laura Cristina; López, Javier; Maulini, Juan Andrés; De Giusti, Armando Eduardo (2011)
Particle Swarm Optimization (PSO) is a metaheuristic that is highly used to solve mono- and multi-objective optimization problems. Two well-differentiated PSO versions have been defined - one that operates in a continuous solution space and one for binary spaces. In this paper, a new version of the Binary PSO algorithm is presented. This version improves its operation by a suitable positioning of the velocity vector. To achieve this, a new modified version of the continuous gBest PSO algorithm is used. The method proposed has been compared with two alternative methods to solve four known test functions. The results obtained have been satisfactory.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Advances in Swarm Intelligence : Second International Conference, ICSI 2011, Chongqing, China, June 12-15, 2011, Proceedings, Part I. Berlín : Springer, 2011. (Lecture Notes in Computer Science ; 6728), pp. 111-119
Keywords: MÉTODOS HEURÍSTICOS; OPTIMIZACIÓN